AJANTA'S DRAWINGS AND COLOR COMBINATIONS (IN THE PERSPECTIVE OF GUPTA ART): अजन्ता के चित्र एवं रंग संयोजन (गुप्तकालीन कला के परिप्रेक्ष्य में) - Dubey, Shraddha (International Journal of Research -GRANTHAALAYAH, 2014)
The Gupta period is called the Golden Age of India's history. In this era of happiness, prosperity and splendor, all arts were equally upgraded. The biggest gift of this era is Ajanta's frescoes. The inaudible works created by painters sitting in deep cenotaphic caves are unmatched. In this, the content and themes were not only taken from the life and Jataka tales of Lord Tathagata, but kept them bound in any limit. In them, hundreds of years of folklore is mirrored like a mirror. In Ajanta, 29 caves have been made by cutting a semi-crescent mountain. It is divided into groups. Among them, the tenth and ninth caves are in the middle group. Most of the pictures of Ajanta caves have been erased, but the remaining ones are amazing. The earliest paintings have the influence of Shung Kala. Lord Tathagata is seated in a view of the ninth cave, King Rani Amatigan and the worshiping monks surround him. Amatyas have turbaned threads at the ends and are wearing heavy jewelery in the hands and neck. With the shapes, they appear to be people of a primitive caste from the south. We can call it the earlier tradition of Ajanta painting. There is more use of gray color in it, but due to the use of natural colors, every object can be seen clearly as above. Due to the lack of bright colors, they reveal the plot seriously and give impetus to its spiritual nature. गुप्तकाल भारत के इतिहास का स्वर्ण-युग कहा जाता है। सुख समृद्धि और वैभव के इस काल में सभी कलाओं का समान रूप से उन्नयन हुआ। इस युग की सबसे बड़ी देन है अजंता के भित्तिचित्र। चित्रकारों ने गहन अधंकरामयी गुफाओं में बैठकर जिन अपार्थिव कृत्तियों का सृजन किया वे अप्रतिम है। इनमें कथावस्तु और विषय तो भगवान तथागत के जीवन और जातक कथाओं से ही लिए किन्तु उन्हें किसी सीमा में बांध कर नहीं रखा। उनमें सैकड़ों वर्षों का लोकजीव दर्पण की भाँति प्रतिबिम्बित है।अजंता में अर्ध-चन्द्राकार पर्वत को काटकर 29 गुफाएँ बनाई गई है। यह समूहों में बंटी हुई है। इनमें दसवीं और नवीं गुफाएँ बीच के समूह में है। अजंता की गुफाओं के अधिकांष चित्र मिट चुके हैं परन्तु जो शेष है वे अद्भुत हैं। सबसे पुराने चित्रों पर शुंग कला का प्रभाव है। नवीं गुफा के एक दृश्य में जो मिट सा गया है भगवान तथागत बैठे हैं, राजा रानी अमात्यगण और उपासक भिक्षु उन्हें घेरे हुए हैं। अमात्यों के सिरों पर लटूदार पगड़ियाँ है और वे हाथों और गले में भारी-भारी आभूषण पहने हैं। आकृतियों से वे दक्षिण की ही किसी आदिम जाति के लोग लगते हैं। इसे हम अजंता चित्रकला की पूर्व परम्परा कह सकते हैं। इसमें धूसरित रंग का प्रयोग अधिक है किन्तु प्राकृतिक रंगों के प्रयोग की वजह से प्रत्येक वस्तु ऊपर वर्णानुसार स्पष्ट नजर आती है। चटख रंग न होने की वजह से यह कथानक को गंभीरता से प्रकट करते हैं और उसके आध्यात्मिक स्वरूप को गति प्रदान करते हैं।